Preparation of low molecular weight natural rubber by ozonolysis of high ammonia latex - Kodama Soji; Furukawa Mutsuhisa; Nishi Katsushi (Journal of Rubber Research, 2003)
Depolymerisation of natural rubber (NR) by bubbling ozone into high ammonia latex was attempted in order to prepare liquid natural rubber. NR was found to depolymerise at a faster rate with increasing ozone generation. Addition of hydrogen peroxide to the latex accelerated the depolymerisation of NR. Regardless of added hydrogen peroxide concentration, when the pH of latex was above 8 at the initial stage of reaction, the rate of depolymerisation was remarkably rapid. However, subsequently, the reaction abruptly slowed when the pH fell below 8. The decreases in pH was due to the formation of levulinic acid during reaction. These results suggested that the main reaction of the depolymerisation in latex was not direct oxidation by ozone through the formation of ozonide, but radical oxidation by hydroxyl and hydroperoxyl radicals formed by reaction between ozone and hydroxyl ion under basic conditions. It seemed that the very slow depolymerisation below pH 8 was due to the formation of levulinic acid from a terminal of a polymer chain, by direct oxidation of ozone. The minimum weight-average molecular-weight of the depolymerised NR achieved was about 50 000.
Keywords: Depolymerisation; High ammonia latex; Hydrogen peroxide; Levulinic acid; Liquid natural rubber; Molecular-weight; Ozone; Weight-average